Evaluation of Escherichia coli cell disruption and inclusion body release using nucleic acid binding fluorochromes and flow cytometry - Richard D. Medwid; Lara Krebs; Shellie Welch (BioTechniques)
Many types of commercially valuable recombinant proteins produced by fermentation are expressed at high levels in Escherichia coli. Often, high-level expression in the host results in the formation of insoluble inclusion bodies. The release of these intracellular inclusion bodies from E. coli following cell disruption is a requirement for further downstream recovery. The ability to discern between intact unruptured cells and granules released from broken cells can provide valuable information for improving recovery yields in downstream purification. This paper describes a rapid and sensitive cytometry-based method that allows the simultaneous measurement of intact heat-killed E. coli and inclusion bodies using staining with nucleic acid binding fluorochromes.